Elf Dog & Owl Head - Anderson, M. T.; Wu, Junyi (Graphic designer) (Somerville, Massachusetts : Candlewick Press, 2023)
"... a magical adventure about a boy and his dog--or a dog and her boy--and a forest of wonders hidden in plain sight."--Provided by publisher.
Keywords: Dogs -- Juvenile fiction; Magic -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Dogs -- Fiction; Magic -- Fiction; Human-animal relationships -- Fiction; Fantasy; Fantasy fiction